n = 0 ∑ ∞ 2 5 n ( 2 n 4 n )
If the above sum can be expressed in the form b a with a and b coprime positive integers, find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 0 + 9 = 2 9 = 7
Log in to reply
wait a second I am getting 59 because answer is 3 2 ∗ ( 5 ) . Click here .
Log in to reply
How would you get 59? 2 5 / 3 = 2 0 / 9 .
Log in to reply
@Jake Lai – You know I am stupid
Log in to reply
@Department 8 – We all make mistakes, hahaha. I've done worse!
Yeah I've reported the question. Miscalculated the answer.
Log in to reply
what is the right answer? mine or yours? Just asking
Problem Loading...
Note Loading...
Set Loading...
Either by using Newton's generalised binomial theorem, or by differentiating the generating function for Catalan numbers, it can be shown that 1 − 4 u 1 = n = 0 ∑ ∞ ( n 2 n ) u n .
Method 1 :
Note that n = 0 ∑ ∞ ( 2 n 4 n ) x 2 n = 2 1 [ n = 0 ∑ ∞ ( n 2 n ) x n + n = 0 ∑ ∞ ( n 2 n ) ( − x ) n ] = 2 1 [ 1 − 4 x 1 + 1 + 4 x 1 ] . Since in the given sum, x = 5 1 , this gives us 2 1 [ 1 − 4 / 5 1 + 1 + 4 / 5 1 ] = 9 2 0 .
Method 2 :
To isolate the even terms, we can substitute u = i x and take the real part to get
n = 0 ∑ ∞ ( 2 n 4 n ) ( − x 2 ) n = R e ( n = 0 ∑ ∞ ( n 2 n ) ( i x ) n ) = R e ( 1 − 4 i x 1 ) .
If we let 1 − 4 i x 1 = r e i θ , then we have R e ( 1 − 4 i x 1 ) = r cos θ . 1 − 4 i x = r 2 e − 2 i θ , so we have cos 2 θ = r 2 and sin 2 θ = 4 r 2 x . Hence, θ = 2 1 arctan 4 x and r = 4 1 + 1 6 x 2 1 .
Thus,
R e ( 1 − 4 i x 1 ) = r cos θ = 4 1 + 1 6 x 2 cos ( 2 1 arctan 4 x ) = 2 4 1 + 1 6 x 2 1 + cos arctan 4 x = 2 4 1 + 1 6 x 2 1 + 1 + 1 6 x 2 1 = 2 ( 1 + 1 6 x 2 ) 1 + 1 + 1 6 x 2 .
By replacing − x 2 with x , we therefore have the result n = 0 ∑ ∞ ( 2 n 4 n ) x n = 2 ( 1 − 1 6 x ) 1 + 1 − 1 6 x . Since in our given sum x = 2 5 1 , as a result we have
n = 0 ∑ ∞ 2 5 n ( 2 n 4 n ) = 2 ( 1 − 1 6 / 2 5 ) 1 + 1 − 1 6 / 2 5 = 9 2 0 .